2010
DOI: 10.2478/v10038-010-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

Biological Symptoms of Aging in Women Regarding Physical Activity and Lifestyle

Abstract: Purpose. Menopause in many women is related to worse health conditions, increased diseases incidence and body mass. The purpose of this research was to investigate whether the differentiation of the involutional changes related to the climacteric period depends on women's physical activity and selected aspects of lifestyle. The following aging indices were analyzed: age of menopause, value of blood parameters, disease incidence, BMI. Basic procedures. The research, conducted in the health care units, was based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…It can therefore be assumed that older rural women are put more at risk of obesity. With regard to the urban population, the average BMI of rural women is higher (Gacek 2011;Ignasiak et al 2011;Nowak and Ignasiak 2008;Stachoń et al 2010).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It can therefore be assumed that older rural women are put more at risk of obesity. With regard to the urban population, the average BMI of rural women is higher (Gacek 2011;Ignasiak et al 2011;Nowak and Ignasiak 2008;Stachoń et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…In some studies it has been reported that rural women are heavier than their peers in urban areas. Perhaps that characteristic is associated with a specific diet and lifestyle of rural women (Gacek 2011;Stachoń et al 2010;Zając-Gawlak and Polechoński 2007). In our study there were no significant difBrought to you by | EP Ipswich Authenticated | 140.234.255.9 Download Date | 2/26/14 5:06 PM ferences in body weight in the studied age groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, the literature on the subject is also scant in regards to what can be considered as valuable research on the relationships between physical fitness and various aspects of an individual's living environment, which has been suggested to be a very important aspect in this regard [4]. Those studies that were identified focused on the relationship between physical activity and health and quality of life [2,[5][6][7][8][9]. Others discussed the relationships between quality of life and economic status, age, education, martial status, sex, and other factors unrelated to what can be understood as the sphere of physical culture [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…W okresie przekwitania, niezależ-nie od klimakterium, nasilają się procesy inwolucyjne [16], pojawiają się inne zaburzenia endokrynologiczne (niezwiązane z czynnością gonad), a także często stres związany ze zmianą sytuacji rodzinnej i społeczno-ekonomicznej [6]. Czynniki te wspólnie wpływają na rodzaj i nasilenie odczuwania dolegliwości menopauzalnych.…”
Section: Dyskusjaunclassified